Functional Dyspepsia: Current Approaches to Diagnosis and Treatment - Svintsitskyi A. (Львівський клінічний вісник)
Introduction. Functional dyspepsia (FD) is common in the worldwide population. In developed countries, dyspeptic disorders occur in 30.0-40.0% of the population and is responsible for 4,0-5,0% of all appeals to general practitioners. In this case, the lion’s share (60.0-65.0%) refers to FD. Women are more likely to suffer after mental injuries. In Ukraine, the prevalence of FD is 30.0-40.0%, but in reality the number of patients may be higher, as many individuals with similar complaints do not visit a doctor. Aim. To make an overview of modern literature on the problem of FD, the current principles of its diagnosis and treatment. Materials and methods. During the study the content analysis, method of system and comparative analysis, bibliosemantic method of study of the actual scientific research were used. Results. According to the recommendations of the conciliation meeting of the International Working Group on the improvement of the diagnostic criteria of the functional diseases of the gastrointestinal tract diseases (Roman criteria III), the diagnosis of FD may be posed if, for at least three last months (not necessarily in succession), there is one of the following symptoms for the last six months: a feeling of gravity after eating; feeling of early saturation; epileurial pain; heartburn in epigastrium, as well as the absence of organic diseases (including those based on the results of esophagogastroduodenal fibroscopy that would explain these symptoms. Treatment of patients with FD syndrome should be comprehensive and include the measures to normalize the lifestyle, diet, labor, psychotherapeutic methods, and, if necessary, medication. Examination and treatment of the patients with FD usually occurs in outpatient conditions until the disappearance of its manifestations. During remission, patients maintain their ability to work. Dispensary assumes the implementation of recommendations for normalization of lifestyle and medical nutrition, periodic examination of patients (once or twice a year) and timely treatment of relapses of the disease. The prognosis in patients with FD is considered rather favorable. With time, there is a decrease in the severity of complaints, which is caused both by a decrease in stressful effects and by the adaptation of patients to factors that have led to the appearance of clinical symptoms. Spontaneous disappearance of symptoms is noted in about one third of patients. It is believed that the risk of peptic ulcer in patients with FD does not differ from the asymptomatic population. Conclusions. FD is one of the most pressing problems of modern gastroenterology, but many issues are still unresolved and need further study.